Can selection for resistance to OsHV-1 infection modify susceptibility to Vibrio aestuarianus infection in Crassostrea gigas? First insights from experimental challenges using primary and successive exposures. (December 2015) - Azéma, Patrick; Travers, Marie-Agnès; Lorgeril, Julien; Tourbiez, Delphine; Dégremont, Lionel
Abstract Since 2008, the emergent virus OsHV-1µvar has provoked massive mortality events inCrassostrea gigas spat and juveniles in France. Since 2012, mortality driven by the pathogenic bacteriaVibrio aestuarianus has stricken market-sized adults. A hypothesis to explain the sudden increase in mortality observed in France since 2012 is that selective pressure due to recurrent viral infections could have led to a higher susceptibility of adults toVibrio infection. In our study, two OsHV-1-resistant lines (AS and BS) and their respective controls (AC and BC) were experimentally challenged in the laboratory to determine their level of susceptibility toV. aestuarianus infection. At the juvenile stage, the selected lines exhibited lower mortality (14 and 33%) than the control lines (71 and 80%), suggesting dual-resistance to OsHV-1 andV. aestuarianus inC. gigas . Interestingly, this pattern was not observed at the adult stage, where higher mortality was detected for AS (68%) and BC (62%) than AC (39%) and BS (49%). These results were confirmed by the analysis of the expression of 31 immune-related genes in unchallenged oysters. Differential gene expression discriminated oysters according to their susceptibility to infection at both the juvenile and adult stages, suggesting that resistance toV. aestuarianus infection resulted in complex interactions between the genotype, stage of development and immunity status. Finally, survivors of theV. aestuarianus challenge at the juvenile stage still exhibited significant mortality at the adult stage during a second and thirdV. aestuarianus challenge, indicating that these survivors were not genetically resistant.